An Expert System to Aid Classification and Referencing Work in Libraries - Subramanian, K. R.; Kripakaran, P.; Arvinda, K.; Murthy, S. G. K.; Panchapakesan, S. (Journal of Information and Knowledge, 2022)
An Expert System has been designed and implemented on a PC/XT to aid classification and referencing work in libraries. The system has been implemented in Turbo Prolog and the rule-based approach is used. Also, the system uses a database for driving the inference engine to the goal. As such any classification scheme can be adopted to help the librarians in indepth classification of books. A system with appropriate classification procedures is being implemented as a set of rules to drive the scheme faster to the goal. Also the system can be used to help the users by prompts and the answers guiding through authorwise and subject wise referencing work. The system is fully menu driven and prompts to elicit the answers. The subject and branches within the subject are displayed and user is guided to select anyone of them by placing the cursor over the choice.